Editorial: Reproductive Barriers and Gene Introgression in Rice Species, Volume II - Koide, Yohei; Matsubara, Kazuki; Tao, Dayun; McNally, Kenneth L. (Frontiers Media, 2022)
Distant hybridization and introgression undoubtedly play a crucial role in Asian rice (Oryza sativa L.) domestication and diversification and will continue to play an important role as humans face to climate change challenges. The limited genetic variation within current rice varieties necessitates the use of various approaches to improve production under increasingly harsher and more frequent abiotic and biotic stresses resulting from climate change. The wild relatives of Asian cultivated rice represent valuable reservoirs of variation for both traditional breeding and advanced technology breeding such as de novo domestication, redomestication, and gene editing improvement.